Penyuluhan Kesehatan Pengenalan Self-Healing dan Hormon Bahagia pada Residen Rehabilitasi Lapas Perempuan Kota Malang - Anung Putri Illahika; Feny Tunjungsari; Pamela Andria Putri Kusuma Sumarauw; Muh. Rizal Hidayat; Amatullah Rusydah Aqiilah (Yayasan Literasi Sains Indonesia, 2025)
Self-healing is a healing process that involves the body's and mind's ability to work together in restoring well-being. Providing this knowledge helps residents understand how positive thinking, healthy habits, and emotional regulation significantly contribute to the healing process. Happiness hormones play a crucial role in regulating mood, reducing pain, and enhancing a sense of well-being. By understanding how to stimulate these hormones through simple activities such as exercise, meditation, social interaction, and hobbies, residents can harness the body’s natural capabilities to improve their mental state. Stimulating these hormones can help reduce stress, alleviate anxiety, and improve sleep quality all of which are essential in the rehabilitation process. The aim of this study is to increase knowledge about self-healing and happiness hormones among rehabilitation residents, thereby reinforcing a holistic approach to healing. In this study, the researcher conducted face-to-face educational sessions with female rehabilitation residents at the Malang Women’s Correctional Facility. Knowledge was assessed before and after the sessions using questionnaires. The educational sessions, which covered self-healing and happiness hormones, demonstrated an increase in recognition and understanding of these topics. This includes improved awareness of the types of happiness hormones, the benefits of self-healing, and the types of activities that can enhance the release of happiness hormones among the female rehabilitation residents in Malang. These results suggest that direct educational interventions remain an effective method for improving individual understanding.